Efforts to improve writing ability with flashcard learning media in grade II students - Maharani, Melina; Arief, Ardian; Wulandari, Ajeng Risky; Munawarti, Susi; Tolentino, Vera Nathalia G. (Trihayu: Jurnal Pendidikan Ke-SD-an, 2024)
This study aims to improve the writing skills of Grade II students in one of the public elementary schools in Yogyakarta through the use of flashcard learning media. The research design used in this study was classroom action research. This study employs a form of collaborative classroom action research, requiring involvement from other relevant parties, namely Grade II elementary school teachers, who will collectively work on improving learning practices with Grade II elementary school students. The data collection technique used in this study was a test. Then, for data analysis, quantitative data analysis was employed. The results demonstrate that the use of flashcard learning media can enhance the writing ability of Grade II elementary school students. This improvement encompasses their ability to write sentences, use capital letters appropriately, and punctuate sentences correctly. Looking at the two cycles (I and II) of writing ability for Grade II students, it was determined that the average score in cycle I was 75.5, falling within the category of reaching the KKM score, with a percentage of 55.5%. In cycle II, the average writing ability score was 91.9, placing it in the "very good" category, with approximately 94% of students successfully reaching this level.